Analysis of Domestic Violence Related Homicides in Los Angeles County: Media Portrayals, Demographics, and Precipitating Circumstances - Perras, Nicolle (Journal of family violence, 2021)
Intimate partner violence (IPV) remains a pressing public health issue. Nationally, 1 in 5 women and 1 in 10 men have sustained severe physical violence from an intimate partner. Intimate partner homicides (IPH) are the most serious IPV outcome. This study examined documented IPH in Los Angeles County during 2017, analyzing if precipitating circumstances, victim demographics, victim/suspect relationship, and weapon type were related to how often a homicide was reported in online media stories. Cases were identified from the National Violent Death Reporting System (NVDRS), and standardized internet searches identified media articles associated with each case. Victim demographics from NVDRS and media articles were compared using Chi Square tests. Media report frequency, within different categorical predictor values, were examined using ANOVA models. 44 incidents were identified; averaging 5.2 articles per decedent. Univariate analyses showed significant difference in media reporting by poverty level (low versus high socioeconomic status) and presence of preceding argument. Multivariate analyses found significantly more media reports (p = 0.002) for incidents in which a preceding argument is reported, the victim was 30–39 years old and from a low socioeconomic status zip code. From our results certain characteristics of IPH are associated with greater media reporting. Promotion of consistent and responsible IPH media reporting guidelines is an opportunity to reinforce public health messaging and dispel myths. In turn, this will encourage the development of future policies and funding streams across the spectrum of preventing and stopping IPV.